Modern Cardiac Surgical Outcomes in Nonagenarians: A Multicentre Retrospective Observational Study - Weinberg, Laurence; Walpole, Dominic; Lee, Dong Kyu; D'Silva, Michael; Chan, Jian Wen; Miles, Lachlan Fraser; Carp, Bradly; Wells, Adam; Ngun, Tuck Seng; Seevanayagam, Siven; Matalanis, George; Ansari, Ziauddin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background. There have been multiple recent advancements in the selection, optimisation and management of patients undergoing cardiac surgery. However, there is limited data regarding the outcomes in nonagenarians, despite this cohort being increasingly referred for these interventions. The objective of this study was to describe the patient characteristics, management and outcomes of a cohort of nonagenarians undergoing cardiac surgery receiving contemporary peri-operative care. Methods. After receiving ethics approval, we conducted a retrospective observational study of nonagenarians who had undergone cardiac surgery requiring a classic median sternotomy. All operative indications were included. We excluded patients who underwent minimally invasive surgery, transcatheter aortic valve implantation, and surgery on the thoracic aorta. Data were collected from four hospitals in Victoria, Australia, over an 8-year period (January 2012 – December 2019). The primary objective was to assess six-month mortality in nonagenarian patients undergoing cardiac surgery and to provide a detailed overview of postoperative complications. We hypothesised that cardiac surgery in nonagenarian patients would be associated with a six-month postoperative mortality < 10%. As a secondary outcome, we hypothesised that significant postoperative complications (i.e., Clavien Dindo Grade IIIb or greater) would occur in > 30% of patients. Results. A total of 12,358 adult cardiac surgery patients underwent surgery during the study period, of whom 18 nonagenarians (0.15%) fulfilled inclusion criteria. The median (IQR) [min-max] age was 91.0 years (90.0:91.8) [90-94] and the median body mass index was 25.0 (kg/m2) (22.3:27.0). Comorbidities, polypharmacy, and frailty were common. The median predicted mortality as per EuroSCORE-II was 6.1% (4.1:14.5). There were no cases of intra-operative, in-hospital, or six-month mortality. One (5.6%) patient experienced two Grade IIIa complications. Three (16.7%) patients experienced Grade IIIb complications. Three (16.7%) patients had an unplanned hospital readmission within 30 days of discharge. The median value for postoperative length of stay was 11.6 days (9.8:17.6). One patient was discharged home and all others were discharged to an inpatient rehabilitation facility. Conclusion. In this selected, contemporary cohort of nonagenarian patients undergoing cardiac surgery, postoperative six-month mortality was zero. These findings support carefully selected nonagenarian patients being offered cardiac surgery. (Trials Registry: https://www.anzctr.org.au/ACTRN12622000058774.aspx)